Solutions of the neutral differential-difference equation αx′(t)+βx′(t−r)+γx(t)+δx(t−r)=f(t) - Ll. G. Chambers (International Journal of Mathematics and Mathematical Sciences)
Particular solutions and complementary functions are obtained for the functional equation αx′(t)+βx′(t−r)+γx(t)+δx(t−r)=f(t) in the forms of a convolution type integral and of infinite series.